2011
DOI: 10.5222/ankem.2011.35
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Acinetobacter baumannii Strains Isolated from Clinical Samples in an Education and Research Hospital (2008-2010)

Abstract: ÖZETHastanemizde yatan hastaların klinik örneklerinden [2008][2009][2010]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
2
9
0
2
Order By: Relevance
“…The resistance rates determined were Ozdemir et al [21] gentamicin 82%, amikacin 76%, netilmicin 25%, Kurtoglu et al [22] gentamicin 86%, amikacin 52%, İraz et al [20] gentamicin 54%, amikacin 69%, netilmicin 15%. In our study, the resistance rates determined were gentamicin in 77.2%, amikacin in 35.2% and netilmicin in 19.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance rates determined were Ozdemir et al [21] gentamicin 82%, amikacin 76%, netilmicin 25%, Kurtoglu et al [22] gentamicin 86%, amikacin 52%, İraz et al [20] gentamicin 54%, amikacin 69%, netilmicin 15%. In our study, the resistance rates determined were gentamicin in 77.2%, amikacin in 35.2% and netilmicin in 19.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Different results were observed in many tigecycline studies. In a study made by Alpat et al [24] in 2010, no tigecycline resistance was determined and in the studies made in 2011, Ozdem et al [10] determined tigecycline resistance as 5.5% and Kurtoglu et al [22] as 16%. Tigecycline resistance was found 41% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Ülkemizde klinik örneklerden saptanan Acinetobacter spp. izolatları meropeneme % 2-76 ve imipeneme % 23-90 oranında dirençli bildirilmişlerdir (3,18,23,37) . Zarakolu ve ark.…”
Section: Discussionunclassified
“…Susceptibilities against imipenem, amikacin, gentamicin, ceftasidime and ciprofloxacin were; % 38, % 14, % 21, %9 and %11 respectively. Kurtoglu et al [6], inspected the resistance rates between 2008 and 2010 in Acinetobacter strains. They found that the resistance rates were inreasing in trimethoprim/sulfamethoxazole, imipenem, piperacillin/tazobactam and sulbactam/cefoperazone by time.…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter species are colonized over mechanical instruments, colonized on health care workers and patients, selected by antibiotic usage and becomes the reason of nosocomial infections [5]. Acinetobacter species are the reason of bacterial colonization, bacteremia, pneumoniae, urinary tract infections, wound infections [6]. In this study it was aimed to investigate the antibiotic susceptibilities and extended spectrum beta lactamase production of Acinetobacter baumanii strains isolated from miscellaneous clinical samples sent to Tavsanli State Hospital Microbiology Laboratory retrospectively.…”
Section: Introductionmentioning
confidence: 99%